Genomic insights into virulence factors affecting tissue-invasive Klebsiella pneumoniae infection - Takashi Matono; Masatomo Morita; Nodoka Nakao; Yuji Teshima; Makoto Ohnishi (BMC, 2022)
Abstract Background The key virulence factors responsible for hypervirulent Klebsiella pneumoniae (hvKp) infection remains elusive. Methods We analyzed K. pneumoniae isolates collected between 2017 and 2019 and defined hvKp as a pyogenic infection. Classical K. pneumoniae (cKp) involved a non-invasive infection or uncomplicated bacteremia. Isolates belonging to the K. pneumoniae species complex were excluded. Results We analyzed 112 isolates, including 19 hvKp, 67 cKp, and 26 colonizers, using whole-genome sequencing. Population genomics revealed that the K1-sequence type (ST) 82 (O1v1) clade was distinct from that of the K1-ST23 (O1v2) clone. The virulence gene profiles also differed between K1-ST82 (aerobactin and rmpA) and K1-ST23 (aerobactin, yersiniabactin, salmochelin, colibactin, and rmpA/rmpA2). The K2 genotype was more diverse than that of K1. A neighboring subclade of K1-ST23 (comprising ST29, ST412, ST36, and ST268) showed multidrug resistance and hypervirulence potentials. Logistic-regression analysis revealed that diabetes mellitus was associated with K. pneumoniae infection (odds ratio [OR]: 4.11; 95% confidence interval [CI]: 1.14-14.8). No significant association was found between hvKp diagnosis and clinical characteristics, such as diabetes mellitus or community acquisition. However, the K1 genotype (OR: 9.02; 95% CI: 2.49-32.7; positive-likelihood ratio [LR]: 4.08), rmpA (OR: 8.26; 95% CI: 1.77-38.5; positive LR: 5.83), and aerobactin (OR: 4.59; 95% CI: 1.22-17.2; positive LR: 3.49) were substantial diagnostic predictors of hvKp. Conclusions The K1 genotype, rmpA, and aerobactin are prominent predictors of hvKp, suggesting that further pyogenic (metastatic) infection should be examined clinically. These findings may shed light on key hvKp virulence factors.